(untitled) (Research, Society and Development, 2022)
Tomato production has been enhanced significantly by management using intervention of temperature and radiation control in a protected environment. The use of plastic and/or polycarbonate covers changes the dynamics of production in tropical climate regions. The present study aimed to compare the following covered cultivation conditions: 1) polycarbonate plate (10 mm) box-shaped polycarbonate with a twin wall with anti UV-A and B (P), 2) agricultural film (AF) anti UV-A and UV-B, and 3) open field (OF) on the productivity and quality of Italian hybrid tomatoes. The study was carried out at Embrapa Agrossilvipastoril located in Sinop, Mato Grosso, Brazil. Four tomato hybrids and 03 distinct environments were used in a randomized block design in a subplot setup with five replications. The main factor was hybrid traits, and the subplots were environments with different covers. The highest productivity occurred in the P environment, with the hybrids Fascinio and Vedette with 66.64 and 55.84 t ha-1, respectively. The highest plant yield obtained was in the P environment, with an average of 3.15 kg per plant. Among the evaluated hybrids, the highest antioxidant potential was observed in Shanty, and for the content of carotenoids, lycopene, and vitamin C, no significant difference was observed between the evaluated hybrids. We can conclude that the use of polycarbonate plates box shaped with a twinwall or agricultural film in a protected tomato cultivation system under high temperature conditions increases the yield and qualitative potential of the Fascinio and Vedette hybrids.